Recent Publications (Quarterly Journal of Economics, 1970)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 84, Issue 3, August 1970, Pages 536–538, https://doi.org/10.1093/qje/84.3.536 Published: 01 August 1970